Rocky Mountain Spotted Fever–Associated Myocarditis - Camily Morales Lopez; Eric C. Zuberi; Michael A. Acevedo Monsanto; Libardo Rueda Prada; Melissa P. Cortes (Annals of Internal Medicine: Clinical Cases)
A previously healthy 23-year-old enlisted man presented for 2 days of fever, gastrointestinal symptoms, cough, and disseminated rash involving the palms and soles. Initial evaluation revealed leukocytosis, elevated liver enzymes, and hyponatremia. Despite antibiotic therapy for pneumonia, his condition worsened, with development of bilateral pleural effusions and myocarditis. After treatment with doxycycline, methylprednisolone, and furosemide, his symptoms improved. He completed a 7-day antibiotic course. Rocky Mountain spotted fever serology was positive 5 weeks after symptom onset. This case highlights the importance of maintaining a broad differential diagnosis and remaining vigilant for atypical presentations of infections to prevent life-threatening complications.